PEMODELAN PERIODIK DAN STOKASTIK UNTUK MENGANALISIS DATA CURAH HUJAN YANG HILANG MENGGUNAKAN STUDI KASUS STASIUN HUJAN SUKARAME - Ashruri Ashruri (UNIVERSITAS LAMPUNG, 2015)
Rainfall data is very important for planning in engineering, especially for hydrology buildings such as water irrigation, dams, urban drainage, ports, docks, etc. Rainfall has periodic and sto - chastic parts, and influenced by climatic parameters such as temperature, wind direction, humid- ity, etc. These parameters are transferred into the periodic and stochastic rainfall components. The rainfall is calculated to determine both, periodic and stochastic components. The missing data were caused by the malfunction of operation of the recording in the rain stations or human error itself.